Development of a novel treatment strategy for the removal of cadmium from wastewater samples using poly(vinyl alcohol)-based magnetic hydrogel beads - Karlidag, Nazime Ebrar; Gover, Tugce; Er, Elif Ozturk; Bozyigit, Gamze Dalgic; Turak, Fatma; Bakirdere, Sezgin (SPRINGER, 2024)
This study proposed a treatment strategy based on the application of poly(vinyl alcohol)-based magnetic hydrogel (PVA-MH) beads for the adsorptive removal of cadmium from synthetic domestic wastewater. The hydrogels were prepared through a facile and rapid synthesis procedure and used to remove cadmium ions from domestic wastewater. The influential parameters of adsorption process were studied by varying the type and volume of buffer solution, mass of adsorbent, and shaking period. The optimum parameters of the adsorption process were found as 1.0 mL of pH 8.0 buffer solution, 100 mg of PVA-MH beads, and 30 min orbital shaking. The process of adsorption equilibrium was clarified by the three-parameter Sips model, and outcomes indicated that this model, with an R2 value of 0.9876, fitted the experimental data effectively. Moreover, sorption kinetic results are well described by the pseudo-second-order kinetic model. The findings indicated that both monolayer adsorption and multi-site interactions governed the adsorption of cadmium onto the hydrogel surface and the swelling characteristics of PVA-MH beads had a low influence on the adsorption mechanism.
Keywords: Adsorption; Cadmium; Domestic wastewater; Flame atomic absorption spectrometry; Hydrogel; Isotherm models; HEAVY-METAL IONS; HUMIC-ACID; ADSORPTION BEHAVIOR; CD(II); ADSORBENTS; KINETICS; SORPTION; PB(II); NI(II); Chemistry; Science & Technology - Other Topics; Materials Science